Enhancing Writing Proficiency through AI-Powered Feedback: A Quasi-Experimental Study Using Google Gemini - S, Kartika (LinguaEducare: Journal of English and Linguistic Studies, 2024)
The use of Artificial Intelligence (AI) in education has gained attention for its potential to enhance student learning, yet limited research has focused on AI-powered tools for providing comprehensive feedback on writing. Most existing studies have concentrated on grammar correction, leaving a gap in understanding how AI can support broader writing development. This study aimed to examine the effect of Google Gemini, an AI-powered chatbot, on writing proficiency in a higher education setting, focusing on grammar, vocabulary, coherence, and task achievement. A quasi-experimental design was used with two groups of 40 students from the Sharia Faculty at UIN Raden Intan Lampung. The experimental group used Google Gemini for writing feedback, while the control group received traditional instruction. Both groups completed pre- and post-test writing tasks, assessed using a standardized rubric. Data were analyzed with paired-sample t-tests to compare improvements between groups. The results showed that the experimental group made significantly greater gains in writing proficiency than the control group, especially in grammar, vocabulary, and coherence. Students in the experimental group also reported higher satisfaction with the immediate, personalized feedback from the AI chatbot. The control group showed modest improvements with traditional feedback, but these were less pronounced. This study suggests that AI tools like Google Gemini can effectively improve writing skills by offering real-time, personalized feedback. It highlights the potential for AI to complement traditional teaching methods, though future research with larger and more diverse samples is needed to explore its impact on higher-order writing skills and across various educational contexts